(untitled) (Revista Contexto & Educação, 2022)
The current research, talks about the training and inserting of educators in the professional and tecnological education (EPT), from the understanding that historically a priority was given to form bachelors. This aspect represents one of the challenges to the expansion and consolidation of the federal network, which needs changes in other educational sectors in order to answer the new political-pedagogical requirements. The article analyses decisive historical land marks to the field conformation, and checks out some legislation devices as well as brazilian educational literature. It questions about the profile of the EPT teacher, build upon the receive heritage and in conflict with the curent necessities, and the pedagogical ideals. It seems there is a consensus around the distancing process of licenciate degree regarding those who starts in the EPT field, in the end some aspects of this Hiatos created by this research will be presented, as well as the urgency of decreasing this distancing aspect.